Pertanggungjawaban BPOM Dan Perusahaan Farmasi Dalam Penggunaan Obat Syrup Anak yang Terkontaminasi Bahan Kimia Berbahaya - Fadli Hamdi; Robi Syafwar (CV. ITTC INDONESIA, 2024)
Many companies produce modern drugs by mixing chemicals so that modern drugs have considerable side effects for humans who consume them. The phenomenon of atypical progressive acute kidney cases (GGAPA) in 2022. First, on October 22, 2022, there were cases of acute kidney disorders, the number of which increased significantly from January to August to 36 cases. However, in September and October, the cases increased again quite rapidly reaching 78 and 110 cases respectively. BPOM is a state Institution that has the authority to control, pay attention to, and supervise the circulation of drugs in Indonesia to ensure the quality of safe and quality drugs in accordance with Presidential Regulation No. 8 of 2017. The purpose of this study is to determine the form of liability of BPOM in the use of children’s syrup contaminated with hazardous chemicals and to determine the form of liability of Pharmaceutical Companies in the use of syrup. This research method uses a normative method with a descriptive approach. The data source in this research uses qualitative data, which is obtained from literature studies and secondary data in the form of primary, secondary, and tertiary data materials. Data analysis using qualitative data analysis techniques. The results showed that the form of legal responsibility of BPOM is to strengthen the pre-market and post-market supervisory functions for the circulation of drugs that conduct clinical testing independently. In addition, the form of legal responsibility of Pharmaceutical Companies is that they must be fully and absolutely responsible for advertising and informing in detail regarding product information that they want to produce and disseminate to the public.